BUDAYA INDONESIA DALAM VIDEO KLIP COLDPLAY “AMAZING DAY” (ANALISIS SEMIOTIKA ROLAND BARTHES) - Antonio C. A. Amaral (Universitas Tribhuwana Tunggadewi, 2019)
Abstract:In communication science the role of art is the content of messages in form of visual, audio, audiovisual. The purpose of this study was to find out Indonesian culture in the Coldplay